2004
DOI: 10.2105/ajph.94.12.2125
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Experiences of Racial Discrimination and Black–White Differences in Preterm and Low-Birthweight Deliveries: The CARDIA Study

Abstract: Mustillo et al. | Peer Reviewed | Research and Practice | 2125 RESEARCH AND PRACTICE  Objectives. We examined the effects of self-reported experiences of racial discrimination on Black-White differences in preterm (less than 37 weeks gestation) and low-birthweight (less than 2500 g) deliveries.Methods. Using logistic regression models, we analyzed data on 352 births among women enrolled in the Coronary Artery Risk Development in Young Adults Study.Results. Among Black women, 50% of those with preterm deliver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
310
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 325 publications
(322 citation statements)
references
References 46 publications
10
310
1
1
Order By: Relevance
“…Our study complements the few existing empirical studies of racism and infant health outcomes. However, not unlike other studies that have investigated racism and birth outcomes, [28][29][30]48 our observed association between racism and low birth weight did not attain statistical significance in adjusted analyses, and therefore our empirical findings are only mildly suggestive of a relationship. We relied on retrospective selfreports of birth outcomes from a sample birth cohort that cannot be generalized to the counties, and our sample may have been inadequately powered for the measured associations.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…Our study complements the few existing empirical studies of racism and infant health outcomes. However, not unlike other studies that have investigated racism and birth outcomes, [28][29][30]48 our observed association between racism and low birth weight did not attain statistical significance in adjusted analyses, and therefore our empirical findings are only mildly suggestive of a relationship. We relied on retrospective selfreports of birth outcomes from a sample birth cohort that cannot be generalized to the counties, and our sample may have been inadequately powered for the measured associations.…”
Section: Discussioncontrasting
confidence: 98%
“…[21][22][23] Perceived discrimination has been associated with low selfrated mental and physical health, [24][25][26] low birth weight, [27][28][29] and preterm delivery 30,31 among African Americans. Perceived discrimination has also been associated with hypertension 32,33 and smoking, 34 which are risk factors during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that a third of Whites perceived that they had been the direct target of unfair treatment because of race is a somewhat surprising statistic, but it is fairly comparable with White rates reported in other studies (e.g., Krieger et al, 2005;Mustillo et al, 2004), is less than a majority, and is considerably lower than that for African Americans, in accordance with hypothesized racial differences. In addition, the African Americans and Whites studied here exhibited a similar pattern of association between perceived racism and the other stress variables (for Whites, rs ranged from .24 for pregnancy anxiety to .44 for stressful life events; for African Americans, rs ranged from .29 for pregnancy anxiety to .53 for stressful life events), suggesting that racism is a form of stress that can be validly assessed in both groups.…”
Section: Discussionsupporting
confidence: 77%
“…Research on stressors for African American women reveals that during pregnancy, they anticipate their children experiencing racial inequalities which includes the possibility of negative police interactions. The psychosocial stress produced by racial and gendered inequities is associated with disproportionately higher rates of adverse birth outcomes among African American women, regardless of their socioeconomic position [11][12][13][14][15][16]. Studies have also revealed significant associations between intersectional racial and gendered stress (that includes parenting demands) and antenatal depression [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%